Bacterial community structure and gene function prediction in response to long-term running of dual graphene modified bioelectrode bioelectrochemical systems. (August 2020) - Chen, Junfeng; Liu, Yanyan; Yang, Yuewei; Tang, Meizhen; Wang, Renjun; Jiang, Liting; Tian, Yuping; Hu, Hanwen; Zhang, Xiao; Wei, Yushan
Graphical abstract: Highlights: Bacterial community and gene function analysis were explored in LT D-GM-BE BES. Maximum power density of LT D-GM-BE BES was 99.03 ± 3.64 mW/m 2, 3.66 times of LT C-BE BES (2 year) Proteobacteria/Firmicutes were dominant phylum in LT GM-BA, Armatimonadetes in LT GM-BC. Dominant bacteria in LT GM-BA was Clostridium, GM-BC was Chthonomonas in genus. Gene function for substrate, energy metabolism and environmental adaptation were enriched. Abstract: This work studied bacterial community structure and gene function prediction in long-term running of dual graphene modified bioelectrode bioelectrochemical systems (LT D-GM-BE BES, 2 year). The maximum power density of LT D-GM-BE BES was 99.03 ± 3.64 mW/m 2, which was 3.66 times of dual control BES (D-C-BE BES), and the transfer resistance of LT GM-BE was just approximately 1/4 of control bioelectrode (C-BE). Proteobacteria and Firmicutes were dominant bacteria in long-term modified bioanode (LT GM-BA, 30.03% and 45.64%), and in long-term modified biocathode (LT GM-BC) was Armatimonadetes (47.14%) in phylum level. The dominant bacteria in LT GM-BA was Clostridium (30.56%), in GM-BC was Chthonomonas (47.14%) in genus level. Gene function related with substrate, energy metabolism and environmental adaptation were enriched. LT GM-BE was tended to enrich dominant bacteria and enrich gene to adapt to micro-environmental changes. This study would provide metagenomics information for long-term running of BES in future.